1990
DOI: 10.1111/j.1365-2672.1990.tb01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and extracellular enzyme production by strains of Bacillus species isolated from fermenting African locust bean, iru

Abstract: Adeiubigbe, E.Y. & Odunfa, S.A. 1990. Growth and extracellular enzyme production by strains of Bacillus species isolated from fermenting African locust bean, iru. Journal of Applied Bacteriology69, 662–671. Seven strains of Bacillus subtilis group, isolated from fermented African locust bean (iru), were screened for proteolytic activity. Three strains (BS2, BL2 and BP2), which were found to be highly proteolytic, were compared on the basis of growth and extracellular enzyme production in media with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
4
18
1
Order By: Relevance
“…This suggests that the bacterial starter culture might have little (or no) effect on fatty acid concentration. This is in agreement with previous research describing that most Bacillus species do not have (or slightly have) lipase enzyme activity (Aderibigbe, Odunfa, 1990;Omafuvbe et al 2000;Chukeatirote et al 2006).…”
Section: Resultssupporting
confidence: 94%
“…This suggests that the bacterial starter culture might have little (or no) effect on fatty acid concentration. This is in agreement with previous research describing that most Bacillus species do not have (or slightly have) lipase enzyme activity (Aderibigbe, Odunfa, 1990;Omafuvbe et al 2000;Chukeatirote et al 2006).…”
Section: Resultssupporting
confidence: 94%
“…isolated from iru to carry out amylolytic, lipolytic and proteolytic activities (Figure 1) was in agreements with the report of Mossel (1982), that Staphylococcus spp. isolated from foods produced extracellular enzymes of which lipase is a major; this is however in contrast with the report of Aderibigbe and Odunfa (1990), who reported that no extracellular lipolytic activity was detected for some Bacillus spp. isolated from iru, when grown in nutrient broth.…”
Section: Moisture Contentcontrasting
confidence: 89%
“…It is generally accepted that proteolysis due to Bacillus spp. results in the production of amino acids and ammonia from proteins which is responsible for the increase in pH during alkaline fermentations (Aderibigbe and Odunfa 1990;Ouoba et al 2003b).…”
Section: Proteinsmentioning
confidence: 97%
“…The main poly-and oligosaccharides contained in some of the seeds are stachyose, raffinose, sucrose and arabinogalactan (Aderibigbe et al 1990;Karr-Lilienthal et al 2005;Kiers et al 2000;Odunfa 1983;Terlabie et al 2006). In addition soybean seeds contain verbascose (Karr-Lilienthal et al 2005).…”
Section: Carbohydratesmentioning
confidence: 99%